AUDIOBOOK SEBAGAI MEDIA ALTERNATIF DALAM REVITALISASI MASATUA BALI - I Gusti Ngurah Agung Wijaya Mahardika (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2017)
The advancement of technology has brought changes in the use of Balinese language for the Balinese. The Balinese language has been set aside in numerous domains of life. To conserve and preserve the existence of Baline language, steps need to be taken in accommodating said advancement of technology to attract the younger generation interest. This paper discusses the idea to use audiobook as a medium to revitalize the masatua Bali (Balinese story telling) tradition as a form of language exposure to the young learners. The use of satua Baliaudiobook should follow the six principles of delivering audio materials and abide to the systematic steps of pre-listening, while listening, and post-listening steps. This steps would ensure the attainment of multiple benefits of the satua Baliaudiobook, namely, exposure of Balinese language to the young learners, fostering the noble values in satua Bali, and at the same time improving the quality of emotional relationship between the parents and the children